2020
DOI: 10.7717/peerj.8665
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of excessive mitophagy by N-acetyl-L-tryptophan confers hepatoprotection against Ischemia-Reperfusion injury in rats

Abstract: In order to investigate the mechnism of hepatoprotective of N-acetyl-L-tryptophan (L-NAT) against ischemia-reperfusion (I/R) injury, the effects of L-NAT were investigated in hepatic ischemia-reperfusion injury (HIRI) models both in vitro and in vivo, which were made by BRL cells and Sprague-Dawley (SD) rats, respectively. The cell viability of hepatocyte was assessed by cell counting kit-8 (CCK-8) staining. The activation of autophagy was detected by electron microscopy (EM), quantitative real-time PCR (qRT-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Previous studies have confirmed that CI/R injury can include the secretion of neuroinflammatory and excessive production of oxidative stress, thereby aggravating brain injury [18]. The results showed that ROS and MDA levels in MCAO model rats were increased, and the levels of SOD were decreased (p < 0.001, Fig.…”
Section: Inhibition Of Hcg11 Alleviated Oxidative Stress and Neuroinf...mentioning
confidence: 58%
“…Previous studies have confirmed that CI/R injury can include the secretion of neuroinflammatory and excessive production of oxidative stress, thereby aggravating brain injury [18]. The results showed that ROS and MDA levels in MCAO model rats were increased, and the levels of SOD were decreased (p < 0.001, Fig.…”
Section: Inhibition Of Hcg11 Alleviated Oxidative Stress and Neuroinf...mentioning
confidence: 58%
“…Previous results of our laboratory showed that SP aggravated the oxidative damage of NSC-34 cell and L-NAT could not only prevent the secretion of SP, but also inhibit the activation of Caspase-1 and IL-1β, indicating that L-NAT may be the effective agent in the treatment of ALS (Sirianni et al, 2015). Used partial HIRI animal models and H 2 O 2 -induced BRL cell oxidative injury models, we not only observed the protective effect of L-NAT on HIRI (Wang et al, 2019); (Li et al, 2020a), but also demonstrated its protection on the striatum and intestinal injury induced by HIRI (Wang et al, 2017;Zhao et al, 2016). At present, the molecular mechanisms underlying the hepatic-protection of L-NAT remains unknown.…”
Section: Discussionmentioning
confidence: 69%
“…Rats were allowed free access to water, while fasted 12 h before surgery. According to previous studies, rats in the I/R + L-NAT group administrated L-NAT at a dose of 10 mg/kg through intraperitoneal injection, while those in the sham and I/R groups were given the same volume of saline 30 min before surgery ( Li et al, 2020a ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the effect of CET on autophagy was further investigated. Mitophagy is a major pathway for the elimination of damaged mitochondria [ 20 ]. Therefore, we speculated that CET might affect the mitophagy or autophagy.…”
Section: Resultsmentioning
confidence: 99%